True Cost of Solar Hydrogen. Issue 5 (18th September 2021) - Vartiainen, Eero; Breyer, Christian; Moser, David; Román Medina, Eduardo; Busto, Chiara; Masson, Gaëtan; Bosch, Elina; Jäger-Waldau, Arnulf
Abstract : Green hydrogen will be an essential part of the future 100% sustainable energy and industry system. Up to one‐third of the required solar and wind electricity would eventually be used for water electrolysis to produce hydrogen, increasing the cumulative electrolyzer capacity to about 17 TWel by 2050. The key method applied in this research is a learning curve approach for the key technologies, i.e., solar photovoltaics (PV) and water electrolyzers, and levelized cost of hydrogen (LCOH). Sensitivities for the hydrogen demand and various input parameters are considered. Electrolyzer capital expenditure (CAPEX) for a large utility‐scale system is expected to decrease from the current 400 €/kWel to 240 €/kWel by 2030 and to 80 €/kWel by 2050. With the continuing solar PV cost decrease, this will lead to an LCOH decrease from the current 31–81 €/MWhH2, LHV (1.0–2.7 €/kgH2 ) to 20–54 €/MWhH2, LHV (0.7–1.8 €/kgH2 ) by 2030 and 10–27 €/MWhH2, LHV (0.3–0.9 €/kgH2 ) by 2050, depending on the location. The share of PV electricity cost in the LCOH will increase from the current 63% to 74% by 2050. Abstract : Green hydrogen will be the main fuel for the future 100% sustainable energy and industry system. Herein, the levelized cost development of utility‐scale solar hydrogen is projected from 2021 to 2050 for ten locations around the world with the help of learning‐curve models for solar photovoltaic and water electrolysis systems.